Relationship Among Fungi Associated with Whole and Rotting Solanum Lycopersicum L. and Two Capsicum Species from Different Locations - Sobowale, Ayodele Adegboyega; Omole, Iyanuoluwa Deborah; Olawuyi, Odunayo Joseph (European Journal of Applied Sciences, 2022)
The relationship among fungi associated with whole and rotting Solanum lycopersicum L., and two capsicum species was examined. Whole (healthy looking) and rotting vegetable fruits (Solanum lycopersicum L., Capsicum annum L. and Capsicum chinense) were obtained from three different units within two markets (Atakumosa and Bodija) in two different states (Osun and Oyo) and brought to the laboratory under sterile conditions. Cut sections from the whole and rotting samples were cultured on Acidified Potato Dextrose Agar (APDA) and incubated at 300C ± 20C for 7 days. Growing fungi were sub-cultured on fresh APDA Petri plates to obtain pure cultures. All experiments were done in triplicates. After identification, each fungus was recorded as present (1) or absent (0). Molecular identification were carried out by DNA barcoding using the ITS region sequencing. The ITS rDNA sequences were compared to those in database using NCBI blast and the genetic distance were used to compare the relationship. Data collected were analyzed using descriptive statistics at p≤0.05. Thirty two fungi were obtained and were identified into nine different genera. These were Saturnispora diversa, Kodamea ohmerii, Pichia kudravizevii, Geotrichum candidum, Aspergillus japonicus, Candida sorboxylosa, Aspergillus niger, Penicillium chrysogenum, Fusarium oxysporum, Rhizopus oryzae, Aspergillus flavus and Penicillum rubens. Pichia kudravizevii had the highest incidence in the whole and rotting fruits. Pencillium chrysogenum, Rhizopus oryzae, Geotrichum candidum, Pichia kudravizevii and Fusarium oxysporum were isolated from both whole and rotting fruits obtained from the two locations. The genera Aspergillus, Pencillium, Fusarium, Rhizopus, Candida and Pichia isolated from Solanum lycopersicum L., Capsicum annum L. and Capsicum chinense obtained from the different locations were genetically related. The genera Saturnispora, Kodamea and Geotrichum obtained from the different locations were also genetically related. Fungal isolates of different genera from different pepper and tomato samples obtained from different locations can sometimes be genetically related. Fungal isolates of the same genus obtained from different locations can also be genetically related.